Further investigations into the genotoxicity of quinoxaline-di-N-oxides and their primary metabolites. (July 2016) - Liu, Qianying; Zhang, Jianwu; Luo, Xun; Ihsan, Awais; Liu, Xianglian; Dai, Menghong; Cheng, Guyue; Hao, Haihong; Wang, Xu; Yuan, Zonghui
Abstract: Quinoxaline-di- N -oxides (QdNOs) are potential antibacterial agents with a wide range of biological properties. Quinocetone (QCT), carbadox (CBX), olaquindox (OLA), mequindox (MEQ) and cyadox (CYA) are classical QdNOs. Though the genotoxicity of parent drugs has been evaluated, the genotoxicity of their primary N → O reduced metabolites remains unclear. In the present study, a battery of four different short-term tests, mouse lymphoma assay (MLA), Ames test, chromosomal aberration assay in vitro and bone marrow erythrocyte micronucleus assay in vivo was carried out to investigate the genotoxicity of the six primary N → O reduced metabolites. Additionally, the genotoxicity of five parent drugs was evaluated by the MLA. Strong genotoxicity of N 1-MEQ, B-MEQ and B-CBX was found in three of the assays but not in the Ames assay, and the rank order was N 1-MEQ>B-MEQ>B-CBX that is consistent with prototype QdNOs. Negative results for the five QdNOs were noted in the MLA. We present for the first time a comparison of the genotoxicity of primary N → O reduced metabolites, and evaluate the ability of five QdNOs to cause mutations in the MLA. The present study demonstrates that metabolites are involved in genetic toxicity mediated by QdNOs, and improve the prudent use of QdNOs for public health. Highlights: MLA, Ames, CA, and MN test were used to reveal genotoxicity of six QdNOs metabolites. N 1-MEQ, B-MEQ and B-CBX have genotoxicity in three assays but not in the Ames assay. The results of MLA of five QdNOs were negative. The results reveal that metabolites are involved in genotoxicity mediated by QdNOs.